PENGARUH KADAR CAMPURAN ASAM OLEAT DAN ISOPROPIL ALKOHOL TERHADAP SIFAT FISIK DAN PROFIL TRANSPOR PATCH KALIUM LOSARTAN DENGAN MATRIKS POLIVINIL ALKOHOL DAN POLIVINILPIROLIDON - , MICHRUN NISA, Dr. Akhmad Kharis Nugroho, M.Si., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Delivery of losartan in a transdermal patch dosage form is challengging in terms of formulation due to losartanâs low bioavailability and short elimination. This study aimed to compare and to assess the effects of oleic acid and isopropyl alcohol with concentration of 5% v/v and of 10% v/v in a transdermal patch formulation using polyvinyl alcohol and polyvinylpyrrolidone as matrix. In addition, this study also wanted to know the transport profile of losartan through rat skin membrane experiment. Patch formulas were determined by using the Simplex Lattice Design with software Design Expert version 7.1.6. Physicochemical characteristic including the visual impression, weight, thickness, loss on drying, the moisture uptake, and drug content were determined. The best obtained formula was used to study transport of losartan by using a vertical type diffusion cell and the data observed were analyzed by using programme of WinSAAM version 3.0.3. The results showed that patch the best formula obtained was a formula of enhancer mixture 5% v/v are 4% v/v oleic acid and 1% v/v isopropyl alcohol, for enhancer mixture 10% v/v are 2,68% v/v oleic acid and 7,31% v/v isopropyl alcohol. The results of the physical test were not significantly different between observation and theoretical values at the optimum conditions. Transport test showed that the amount of drug was ready to be transported for enhancer mixture 5%v/v into the skin was 15.51 Âµg, while the enhancer mixture 10%v/v was 28.17 Âµg. In adition, lag time enhancer mixture 5% v/v start at 12 hours, while the lag time enhancer mixture of 10% v/v start at 13 hours since the transdermal delivery performed.